Pediatric Hypertension - Portman, Ronald J.; Sorof, Jonathan M.; Ingelfinger, Julie R. (Clinical Hypertension and Vascular Diseases, 2004)
After obesity and asthma, hypertension is the most frequently occurring chronic disease in childhood, as well as an important precursor of adult cardiovascular disease. In Pediatric Hypertension, a multidisciplinary panel of physicians, clinicians, and academicians comprehensively review all aspects of this disease to create the most state-of-the-art treatment of the subject currently available. The topics covered range from the regulation and assessment of blood pressure in children, to its evaluation and day-to-day management. The authors not only outline the pathophysiology of hypertension in children, but also offer current information on blood pressure measurement, the proper techniques for diagnosis, the assessment of hypertensive end-organ damage even in childhood, and the use of ambulatory blood pressure monitoring. Additional chapters address the genetic background of hypertension, the characterization of the disease from infancy through the teen years, and the appropriate treatment of hypertension-with and without drugs-including details of current studies of antihypertensive medications and their use. Definitions of hypertension in children, predictors of future hypertension, risk factors-race and ethnicity, diet, obesity, and society-and special populations are discussed at length. Comprehensive chapters on both primary and secondary hypertension in children point out differences in presentation between the pediatric and adult populations. Authoritative and current, Pediatric Hypertension offers pediatricians, family practitioners, and pharmaceutical scientists a comprehensive survey of what is currently known about childhood hypertension, as well as detailed practical advice for its optimal management